Vibration-based monitoring and diagnosis of cultural heritage: A methodological discussion in three examples - Ceravolo, Rosario; Pistone, Giuseppe; Zanotti Fragonara, Luca; Massetto, Stefano; Abbiati, Giuseppe (Taylor & Francis, 2014)
Modern monitoring techniques contribute to accurately describing the structural health conditions of historical buildings and to optimizing the plan of maintenance as well as the restoring intervention. Particularly, dynamic testing gives knowledge about global structural behavior and can be used to calibrate numerical models and to predict the response to dynamic and earthquake loading. In some circumstances, vibration-based monitoring can also help in evaluating safety conditions. The present article proposes a discussion about the methodological multidisciplinary approach to modal testing when applied to architectural heritage buildings and structures, along with the description of selected case studies. These examples were chosen to cover the various issues connected to test design and interpretation.
Keywords: Architechural heritage; Dynamic characterization; Experimental modal analysis; Geometrical survey; Modal testing; Model updating; Seismic response